A Syntactical Analysis on Sentence Structure used in Two Adeles’s Songs - Wiyogo Purnomoadjie; Mulyadi Mulyadi (Institut Agama Islam Negeri Madura, 2019)
Syntax is the branch of linguistics that described the sentence structure, songs are composed by a collection of phrases and sentences are also interested to be studied through syntax. This research aims to describe the sentence structure through a tree diagram and to find the sentence structure appears in two Adele’s song, especially in writing a descriptive text. This research employs a descriptive qualitative method. Two kinds of data collection were used to collect the data, those are observation and documentation. In observation, the researcher did something such as listening to the songs “Someone Like You” and “Don’t You Remember” and listening to the songs again focusing on the lyrics. In the documentation, analyzing the lyrics from each song and writing down all the lyrics of two songs to be analyzed use tree diagram. Having analyzed the data, then, finally found sixty forms of the structure of the two Adele’s songs. From the two of Adele’s songs used as the samples in this thesis, grammatical sentence mostly appears rather than an ungrammatical sentence. Through the discussion, the researcher also found the substandard English words, such as Ain’t, you’d, I’ll, you’re, didn’t, couldn’t, isn’t.